Bidirectional associations between parenting styles and conduct problems in Chinese preschool children: the Shenzhen Longhua Child Cohort Study. Issue 9 (21st October 2022) - Guo, Yawei; Zhang, Yu-Qi; Wu, Chuan-An; Yin, Xiao-Na; Zhang, Jing-Yu; Wu, Jian-Bo; Jing, Jin; Jin, Yu; Lin, Li; Chen, Wei-Qing
ABSTRACT: The bidirectional associations between parenting styles and conduct problems in Chinese children attending preschools were rarely discussed. A study covering 171 preschools in Longhua District of Shenzhen, China was conducted among children when they first attended preschools. Parents of children reported the self-perceived parenting styles and their children's conduct problems using validated questionnaires. The bidirectional associations between parenting styles and conduct problems in children were assessed using multivariate linear or logistic regressions in both cross-sectional and cohort settings. In cross-sectional settings, the bidirectional associations were present in all dimensions of parenting styles with children's conduct problems. After 1.01 years of follow-up, increases in parenting dimensions of rejection, control attempts, and favoring subject were significantly associated with children's conduct problems at follow-up, while increases in emotional warmth of parents significantly reduced such risk. In addition, parents of children who had conduct problems at baseline but regressed to normal at follow-up showed decreased scores in negative parenting dimensions. In contrast, among children who developed conduct problems during the study period, the scores of rejection and favoring subject in their parents have increased significantly, while the scores of emotional warmth have decreased. Parent-to-child effect was similar between fathers and mothers, while child-to-parent effect was stronger in fathers than that in mothers. In order to stop the negative feedback loop between poor parenting styles and children's conduct problems, our study underscored the importance of intervention not only in parents but also in their children.